2004
DOI: 10.1017/s0033291703008791
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of Siberian ginseng for chronic fatigue

Abstract: Overall efficacy was not demonstrated. However, the findings of possible efficacy for patients with moderate fatigue suggests that further research may be of value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 32 publications
1
38
0
2
Order By: Relevance
“…the eleutherosides similar to ginsenosides that have effects in the body conforming to its definition as an adaptogen [81]. Specifically, six Eleutherococcus compounds exert adaptogenic effects in the body; four of them act as antioxidants, four exhibit anticancer effects, and two show demonstrable immunostimulatory effects [82,83].…”
Section: Siberian Ginseng (Botanical Name: Eleutherococcus Senticosusmentioning
confidence: 96%
See 1 more Smart Citation
“…the eleutherosides similar to ginsenosides that have effects in the body conforming to its definition as an adaptogen [81]. Specifically, six Eleutherococcus compounds exert adaptogenic effects in the body; four of them act as antioxidants, four exhibit anticancer effects, and two show demonstrable immunostimulatory effects [82,83].…”
Section: Siberian Ginseng (Botanical Name: Eleutherococcus Senticosusmentioning
confidence: 96%
“…The immunostimulatory, antiviral, HPA axis-modulatory and fatiguedelaying effects of Siberian ginseng may serve people with CFS to improve these parameters, thereby alleviating some symptomatology of the syndrome. In a placebo-controlled study in humans [81], it showed moderate benefit in CFS. In another study [85], use of a Siberian ginseng containing a formulation called Ciwujia showed on exercise performance under a constant endurance load of 450 kg × m/min (75 W) that the preparation could increase oxygen uptake, spare the glycogen in muscle, and improve the exercise endurance and work performance in humans.…”
Section: Siberian Ginseng (Botanical Name: Eleutherococcus Senticosusmentioning
confidence: 96%
“…Some showed no difference between Ginseng and placebo on relieving fatigue (13). On the other hand, in a randomized controlled trial of Ginseng for chronic fatigue, fatigue severity and duration were significantly improved in response to Ginseng and treatment was effective at 2 months for 45 subjects who had less severe fatigue among the group of 76 patients studied (14). In addition, Ginseng's ability to enhance cognitive performance in CFS patients was proven in a double-blind, placebo-controlled study (15).…”
Section: Present Evidence To Support the Efficacy Of Tcm In Treating mentioning
confidence: 99%
“…Eleutherococcus senticosus) or Siberian ginseng is a spiny-stemmed shrub belonging to the family Araliaceae. In a placebo-controlled study in humans, it showed moderate benefit in chronic fatigue syndrome (Hartz et al, 2004). Another study, using a formulation containing Siberian ginseng called Ciwujia, on exercise performance showed that under a constant endurance load of 450 kg.m/min (75W), the preparation could increase oxygen uptake, spare the glycogen in muscle and improve the exercise endurance and work performance in humans (Wu et al, 1998).…”
Section: Acanthopanacis Senticosusmentioning
confidence: 99%